2015
DOI: 10.1021/acs.jpcc.5b03286
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Ion Transport in NASICON-Type Electrolytes

Abstract: Herein we report a study on the energetics of ion transport in NASICON-type solid electrolytes. A sol−gel procedure was used to synthesize NASICON-type lithium-ion conductors with nominal compositions Li 1+X Al X Ge 2−X (PO 4 ) 3 where 0 ≤ X ≤ 0.6. Trends in the conductivity and activation energy, including both enthalpic and entropic contributions, were examined with electrochemical impedance spectroscopy. Physical interpretations of these results are drawn from structural characterizations performed by synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
51
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 30 publications
12
51
2
Order By: Relevance
“…The thermal transport behavior of superionic conductors has been studied by a number of numerical models [22,28,29,30] using different approaches. The main results of the modeling can be summarized in the following predictions: The thermal conductivity as a function of the temperature should show the same exponential behavior like the ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal transport behavior of superionic conductors has been studied by a number of numerical models [22,28,29,30] using different approaches. The main results of the modeling can be summarized in the following predictions: The thermal conductivity as a function of the temperature should show the same exponential behavior like the ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, so far, only a few reports were found highlighting the sodium ionic conductors with the NASICON-type structure containing Al cations. 19,25,26 Therefore, the present research reported here, aims at developing the Al-containing NASICON (Na 3 Al 2 P 3 O 12 ) glass for use as a solid electrolyte material by understanding the glass structure and the modications that occur in the structure with the changes in its chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…147 Higher substituent content increases activation energy due to the smaller bottleneck size. 148 Further co-substituting with Y tweaks the microstructure and grain morphology producing a denser product with lower intergrain resistance. 149 Other co-substitution explored on Al-LGP is Sr where due to its large ionic radius has limited solubility of 0.17 per unit formula above which secondary phase (ScPO 4 ) forms at the grain boundary lowering intergrain lithium diffusion.…”
Section: Materials Advances Reviewmentioning
confidence: 99%